Hubungan Modal Sosial Kelompok Tani dan Pendapatan Petani Padi Sawah di Kelompok Tani Desa Sungai Nilau Kecamatan Sungai Manau Kabupaten Merangin - Pitriani Pitriani; Joni Iskandar; Isyaturriyadhah Isyaturriyadhah (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2022)
This research intends to ascertain the social capital and income of rice farmers in Sungai Nilau Village, Manau District, and Merangin Regency, as well as the link between social capital and income. From May 17 to June 17, 2020, this study was conducted in Sungai Nilau village, Manau sub-district, Merangin district. A survey approach was used in this investigation. Of the 233 individuals, samples were obtained from up to 20%. Thus 46 of them were lowland rice growers. During data collection, a simple random sample procedure was applied. The Chi-Square (X2) test technique, income analysis, and the Likert scale are employed in the data analysis. With a total score of 1,999, the findings demonstrated that the social capital of lowland rice farmer groups in Sungai Nilau Village was high. With an average income of IDR 11,080,654.29, lowland rice farmers in Sungai Nilau Village, Sungai Manau District, and Merangin Regency fell into the medium income category. There is a significant relationship between the lowland rice farmer group's social capital and income in these areas, as well as a moderate level of closeness (C = 0.39) (2 counts = 8.16 > 2 table = 5.99).